Pengaruh Edukasi Media Whatsapp Tentang Gizi Laktasi, Involusi Uteri, Dan Lochea Terhadap Pengetahuan, Sikap Dan Perilaku Ibu Nifas - Ratnaeni; Agussalim Bukhari; Healthy Hidayanty; Nurpudji Astuti Daud; Burhanuddin Bahar; Ni Luh Puti Herli Mastuti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2021)
The abnormal period of nifas causes problems such as the sub-involution of utero and bleeding, when it is not handled quickly can result in maternal mortality. Education is one of the upbringing to improve the knowledge, attitudes and behaviors of mother Nifas. The aim of this research is to know the effect of WhatsApp education on lactation, uteri, and Lochea on the knowledge, attitudes and behavior of puerperium in the working area of Sitti Khadijah I Muhammadiyah Makassar